THE CORRELATION BETWEEN PRINCIPALS’ TRANSFORMATIONAL LEADERSHIP, WORK CLIMATE, AND TEACHERS’ SKILL VARIETY AND TEACHERS’ TEAM EFFECTIVENESS IN INTEGRATED ISLAMIC JUNIOR HIGH SCHOOLS IN RIAU ISLANDS PROVINCE - Suntama Putra; Risnita Risnita; Kemas Imron Rosadi; Asrulla Asrulla (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the influence of Transformational Leadership, Work Climate, and Skill Variety on the effectiveness of teacher work teams at Integrated Islamic Junior High Schools in the Riau Islands Province. The research uses a quantitative approach with a survey method. The sample consists of 120 teachers selected through proportional stratified random sampling. The research instrument is a Likert-scale questionnaire that has been tested for validity and reliability. Data analysis was carried out using Spearman correlation tests and non-parametric regression with the aid of SPSS version 29.00. The results show that all independent variables are positively and significantly related to teacher work team effectiveness (Transformational Leadership: ρ = 0.757; Work Climate: ρ = 0.795; Skill Variety: ρ = 0.767; p < 0.05). Non-parametric regression testing indicates a significant simultaneous effect (ρ = 0.000). Partially, Transformational Leadership (p = 0.253; p = 0.000), Work Climate (ρ = 0.355; p = 0.000), and Skill Variety (ρ = 0.282; p = 0.000) significantly influence teacher work team effectiveness. Work climate is proven to be the dominant factor affecting team effectiveness. The implications of this study affirm that improving teacher work team effectiveness must be carried out holistically through strengthening school principals’ transformational leadership, creating a conducive work climate, and developing teachers’ skill variety.